Clinicopathologic and Molecular Features of Metastatic Follicular Thyroid Carcinoma in Patients Presenting With a Thyroid Nodule Versus a Distant Metastasis. (April 2019) - Cracolici, Vincent; Kadri, Sabah; Ritterhouse, Lauren L.; Segal, Jeremy P.; Wanjari, Pankhuri; Cipriani, Nicole A.
Abstract : Metastatic follicular thyroid carcinoma (FTC) is rare. The aim of this study was to determine the clinical, histologic, and molecular differences between patients with metastatic FTC who present with distant metastatic (DM) disease versus those who present with a primary thyroid nodule (PT). Clinical and pathologic information was extracted from the medical record and surgical pathology report. When available, slides were reviewed. Molecular testing was performed on available primary and/or metastatic lesions. Thirty-six patients with metastatic FTC were identified: 15 DM and 21 PT. DM patients were significantly older than those with PT ( P =0.0001). In DM patients, bone was the most common site of initial metastasis ( P =0.03), compared with lung in PT patients ( P =0.03). Unique to primary carcinomas in DM patients was extensive intratumoral fibrosis (50%), occasionally reaching such a degree as to obscure histologic features of malignancy (2 cases). Oncocytic features were more common in those who presented with PT ( P =0.03). Pathogenic mutations were identified in 85% of cases, most commonly in RAS (55%) and TERT promoter (45%); of these, combined RAS and TERT was present in 30%. Pathogenic PTEN, NF1, RET, and BRCA2 mutations were also identified. The prevalence and type of pathogenic mutations did not differ between DM and PT patients. The acquisition of a pathogenic mutation in the metastatic focus that was not present in the primary carcinoma was rare (1 case). In summary, FTC presenting with DM compared with PT was more likely to be present in an older age group, to metastasize to bone, and to demonstrate extensive fibrosis possibly representing histologic regression.